Experimental analysis of fiber optic responses in ionizing radiation environments for distributed sensing applications. (December 2020) - Stratton, Charles; Tsvetkov, Pavel
Abstract: This research explored the use of fiber optics as a distributed sensing dosimeter. It had been demonstrated in previous research that Rayleigh scattering within a fiber increases with radiation dose. Therefore, measuring the increase over a spatial distribution would give a distributed measurement of dose if properly correlated. This is offered by the technology of the Optical Time Domain Reflectometer (OTDR) and the more advanced Optical Frequency Domain Reflectometer (OFDR). As a scoping experimental study with OFDR, an ionizing radiation source was used at different orders of magnitude to irradiate several different test rigs. It was demonstrated at the 1 MGy dose range, the response was a discernible increase in scattering that was distributed spatially in the same manner as the dose, therefore suggesting such use in sensing applications. Graphical abstract: Image 1 Highlights: Rayleigh scattering in fiber optics was measured using an OFDR for gamma radiation doses of different orders of magnitude. Results showed the scattering profile was preserved even at the highest irradiation dose magnitude (1 MGy). At the 1 MGy range, the difference in scattering had a negatively-sloped trendline distributed in the same shape as the dose.